SARS-CoV-2 coinfections with variant genomic lineages identified by multiplex fragment analysis - Lueking, Richard; Clark, Andrew E.; Narasimhan, Madhusudhanan; Mahimainathan, Lenin; Muthukumar, Alagarraju; Larsen, Christian P.; SoRelle, Jeffrey A. (Frontiers in Genetics, 2022)
Immunocompromised patients can experience prolonged SARS-CoV-2 infections in the setting of a lack of protectivity immunity despite vaccination. As circulating SARS-CoV-2 strains become more heterogeneous, concomitant infection with multiple SARS-CoV-2 variants has become an increasing concern. Immunocompromised patient populations represent potential reservoirs for the emergence of novel SARS-CoV-2 variants through mutagenic change or coinfection followed by recombinatory events. Identification of SARS-CoV-2 coinfections is challenging using traditional next generation sequencing pipelines; however, targeted genotyping approaches can facilitate detection. Here we describe five COVID-19 cases caused by coinfection with different SARS-CoV-2 variants (Delta/Omicron BA.1 and Omicron BA.1/BA.2) as identified by multiplex fragment analysis.